The relationships between workload, stress, motivation and performance of nurses' working in the emergency department of public hospitals during the COVID-19 pandemic: A cross-sectional study - Rahmad Gurusinga; Sri Wulan; Karnirius Harefa (Kashan University of Medical Sciences, 2023)
Background: Pandemic conditions increase nurses' workload, trigger stress, decrease motivation, and influence nurses' performance.Objectives: This study analyzed the relationships between workload, stress, motivation, and performance of nurses working in the Emergency Department of Public Hospital during the COVID-19 pandemic.Methods: This was a cross-sectional study. Closed-response questionnaires were used to collect data in this study. The sample consisted of 77 respondents. Data were processed using the chi-square test with a significance of 0.050 and the multiple logistic regression analysis.Results: Nurses were primarily between 30 and 35 years old (64.9%); 70.1% were women, and 70.1% possessed a bachelor's degree. Nurses' performance was significantly associated with workload (P=0.015) and motivation (P=0.019). Trigger stress was not related to the nurses' performance (P=0.066).Conclusion: Workload and motivation are associated with nurses' performance. High motivation from hospital management can significantly affect the nurses' performance by 5.921 times.